Adjunctive Corticosteroid Therapy in Kawasaki Disease: A Meta-Analysis and Trial Sequential Analysis of Randomized Controlled Trials - Abbas Khan; Syed Wajihullah Shah; Sundus Huma; Rimsha Adnan; Muhammad Yahya; Abuzar Khan; Wara Adnan; Usama Habib; Ilsa Khan; Moeen Ikram; Muhammad Awais; Ubaid Ullah; et al. (Cardiology in Review, 2026)
Kawasaki disease is the leading cause of acquired heart disease in children, with coronary artery lesions (CALs) as its most serious complication. Although intravenous immunoglobulin (IVIG) is the standard first-line treatment, some patients develop IVIG resistance or persistent inflammation, increasing the risk of adverse outcomes. This systematic review and meta-analysis evaluated the efficacy and safety of adjunctive corticosteroid therapy in children with Kawasaki disease. PubMed, Embase, and Cochrane CENTRAL were searched through May 2026 for randomized controlled trials comparing IVIG plus corticosteroids with IVIG alone. Outcomes included CAL at approximately 4 weeks, need for additional IVIG therapy, duration of fever, and treatment-related adverse events. Six trials involving 3904 children were included. Compared with IVIG alone, adjunctive corticosteroid therapy significantly shortened fever duration and reduced the need for additional IVIG treatment. However, no significant differences were observed in the incidence of CAL or adverse events. Trial sequential analysis indicated that the available evidence for coronary outcomes remains insufficient, as the required information size has not yet been reached. These findings suggest that corticosteroids improve early clinical response and reduce treatment resistance in Kawasaki disease, but their role in preventing CALs remains uncertain and requires further large-scale randomized trials.